Asking Questions to Learn (2016)
For Daniela Correa Pinto, questioning is the best way to learn, because it makes her doubt what she knows by inheritance and makes her indeed about what she does not yet know, the Children's University has had a great influence on that way of thinking and to find its way into politics.